Three-point integral boundary-value problems for piecewise fractional impulsive differential equations with p-Laplacian operator - Xiao Chen; Wenxue Zhou (Electronic Journal of Differential Equations)
We study the existence and uniqueness of solutions for three-point integral boundary-value problems of piecewise fractional impulsive differential equations with $p$-Laplacian operator and delay. We prove the existence of solutions, by using the $ψ$-Hadamard fractional definition, the Leray-Schauder nonlinear alternative, and the Krasnosel'skiis fixed point theorem. Subsequently, we prove uniqueness of the solution using the Banach fixed point theorem. To verify the feasibility of the main results, we give two examples.